STUDI PENERAPAN BANK SAMPAH DALAM UPAYA PENGELOLAAN LINGKUNGAN HIDUP DI KOTA YOGYAKARTA - Haryanti, Sri; Gravitiani, Evi; Wijaya, Mahendra (Universitas Muhammadiyah Surakarta, 2020)
Waste Bank program is an alternative in waste management by 3R (Reduce, Reuse, Recycle) approach. Yogyakarta is one of the cities that has implemented that program. This study was aimed to analyze the composition of the deposited waste to the banks and examine the implementation of waste banks in Yogyakarta city in environment management efforts. The study was conducted in October-December 2016, and is a quantitative study that was conducted by measurement, interview and observation methods in five waste banks in Yogyakarta City. Data analysis was performed by means of quantitative descriptive in the form of tables and graphs. The results show that total weight of the deposited waste in a month is 3,062.1 kg, in average. The composition of the waste consists of: plastic 23.36%, paper 65.06%, glass 5% and metal 6.56%. The Waste Bank program in Yogyakarta City is able to assist the efforts of environment management, with a potentiton of 97% waste reduction. After the existence of waste banks, in corresponds with their environment condition, 65 respondents (65%) stated it is clean, and 35 (35%) stated very clean. Respondents who stated that their houses are very clean and clean are 34% and 66%, respectively.